Assessment of Siltation Impact and Mitigation Strategies for Sustaining Storage Capacity in Lwanyo Dam, Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
The ongoing generation, transportation, and deposition of silt in the Lwanyo Dam has significantly reduced the storage capacity of the Lwanyo Reservoir, originally constructed to support irrigation and the surrounding ecosystem. The objective of this paper was to assess the extent of siltation in Lwanyo Dam, evaluate its impact on the dam's storage capacity, and propose measures to mitigate silt accumulation. The upstream catchment area, approximately 39.6 km², includes around 128,991 m² allocated for rain-fed crop cultivation and 5.89 km² for pastoral activities. Frequent overtopping of the reservoir has been observed, largely due to siltation reducing its live storage capacity. In the reservoir trial pits were excavated and assessed, and they indicate that average silt layers range in thickness from 0.54 m to 0.98 m per rainy season. The deposited material consists of a silt layer from 0 to 540 mm, followed by an intermediate clay layer from 540 mm to 3100 mm. The impounded silt depth was measured at 1270 mm, with an estimated siltation volume of 58,349.4644 m³. The reservoir's original storage capacity of 210,153 m³ has been reduced by 27.765% due to siltation. The reservoir’s structural design inadequately addresses silt management, lacking both silt flushing tunnels and upstream silt check dams. The analysis indicates that storage capacity decreases by 3.085% annually, and if this linear trend continues without any intervention measures, the dam will lose all storage capacity within 24 years. The study recommends urgent measures to mitigate silt accumulation.